Development of Net Zero Energy Settlements Using Advanced Energy Technologies. (2017) - Synnefa, Afroditi; Laskari, Marina; Gupta, Rajat; Pisello, Anna Laura; Santamouris, Mat
Abstract: The research activities described in this paper focus on the development and implementation of a comprehensive and cost-effective system for Net Zero Energy (NZE) settlements. The system is composed of innovative solutions for the building envelope, for building energy generation, and for energy management at the settlement level. The developed solutions will be implemented in 4 different demonstration projects throughout the EU, with varying climates and building types. The results of their implementation will be monitored, analyzed. The target is to achieve a reduction of operational energy usage to 0-20 kWh/m2 per year through a transition from single NZE buildings to NZE settlements, in which the energy loads and resources are optimally managed. In addition, investment costs will be at least 16% lower than current nZEB costs. In this paper, the methodology that was developed in order to optimize the energy, environmental and cost plans of the four case studies through the best integration and combination of the selected innovative energy technologies with excellent architectural and engineering design is described. In addition the evaluation of the four NZE settlements in terms of energy, environmental and cost performance is presented.